The Influence of Service Quality, Price, and Promotion on Customer Satisfaction and Loyalty for Spotify Premium - Dania Rizqi Ernanda Dania; Sumadi Sumadi (Jurnal Economic Resource, 2023)
The purpose of this research is to analyze the effect analysis of service quality, price, and promotions on customer satisfaction and loyalty on Spotify premium users. The analysis used was the AMOS application program version 26.0. This research was conducted in the city of Yogyakarta. This research is a causality study with variables including service quality, price, and promotions and dependent variables including customer satisfaction and loyalty. The population used is all Spotify premium users in Indonesia. The sampling technique used nonprobability sampling, namely purposive sampling. The number of samples used was 235 respondents and analyzed using the SEM approach. The results of data analysis show that service quality and price have a positive and significant effect on customer satisfaction. Price and satisfaction have a positive and significant effect on customer loyalty. Service quality has a positive and significant effect on customer satisfaction and service quality has a positive and significant effect on customer loyalty.